QCD phenomenology in tachyon condensation theory - Issifu, Adamu (2021)
This thesis is intended to contribute to the long standing problems associated with theoretical QCD theory. We aim at touching on all possible QCD features such as; color confinement, asymptotic freedom and chiral symmetry breaking. We focus on QCD phenomenology by considering an effective theory for Dp-branes at tachyonic vacuum. We will highlight the behaviour of the particles in both the high energy and low energy regions in the framework of the theory. But a particular attention will be devoted to the behaviour of the particles in the IR region where the particles are nonperturbative with a relatively large running coupling. This is intended to enhance the current understanding of nonperturbative QCD. We will study several confining features including; glueball masses, QCD beta function β(Q2 ), the strong running coupling αs(Q2 ), QCD vacuum, vector, scalar and net confining potentials with their associated string tensions. We explore the effect of temperature on the models resulting into thermal deconfinement and restoration of chiral symmetry at higher temperatures beyond the critical temperature of the system. The scalar field that modify the DBI theory is related to tachyons, and it is carefully defined to produce Spontaneous Symmetry Breaking (SSB) of the system. This phenomenon will make it possible to investigate elementary particles, dual superconductivity, glueballs, glueball-meson mix and other phase transitions.